Differences in Mother's Knowledge and Attitudes in the Toddler Mother's Class in Stimulating Child Growth and Development - Stephanie Lexy Louis; Ayu Nina Mirania; Evi Yuniarti (GLOBAL HEALTH SCIENCE GROUP, 2025)
The period of child development is important for the development of cognitive, motor, language, socio-emotional skills, religion, art and morals. The success of the educational process during this period is the basis for the next educational process. Child growth and development monitoring can be carried out through the toddler mothers class program to improve knowledge, attitudes and behaviors of mothers in realizing optimal growth and development of toddlers. In this case, it is important for mothers to have a book on Maternal and Child Health. This study aims to find out the difference in knowledge and attitude of mothers towards the class of mothers under five to stimulate children's growth and development. This type of research is experimental with one group pre test post test design research. The samples in this study were taken in 37 respondent (total sampling) which was carried out to all members of the population as research respondents. The data analysis technique used the Wilcoxon statistical test.The results of the study conducted by taking pretest and postest data found that there was a difference in mother's knowledge as evidenced by a p value = <0.001 and there was a difference in maternal attitudes as evidenced by a p value = <0.001 in the toddler mother's class to stimulate children's growth and development. Advice for mothers to be more routine and active in participating in classes for toddlers in order to achieve optimal growth and development of children.